Mariusz Szram, Wokół osoby i myśli Orygenesa (Lublin: Wydawnictwo KUL 2021) - Czyżewski, Bogdan Stanisław (Verbum Vitae, 2022)
Book review: Mariusz Szram, Wokół osoby i myśli Orygenesa (Lublin: Wydawnictwo KUL 2021). Ss. 477. 55 PLN. ISBN 978-83-8061-928-9